Lecture notes of Relativistic Mechanics: Worldlines, times and velocities of a particle - Carf`ı, David (Journal of Mathematical Economics and Finance; Vol 6 No 1 (2020): JMEF, Volume VI, Issue 1(10), Summer 2020DO - 10.14505/jmef.v6.1(10).04, 2020)
In these notes, we define and study some concepts from Special Relativistic Mechanics, in a differential geometric perspective. Our approach allows us to revisit and rethink some basic theoretical structures, in a way that reveals more feasible to developments in various directions, in particular in view of a better integration with Quantum Mechanics.